Desinformação e sala de aula: inspirações sociológicas para o enfrentamento às fake news no ambiente escolar - Silva, Francisco Fabrício Pereira da (2024)
The main objective of this paper is to provide sociologically-oriented heoretical and methodological support for high school teachers of the humanities and applied social sciences, with the aim of helping to tackle fake news and isinformation in the classroom and the school environment as a whole. We resent a theoretical discussion on the definitions of fake news, digital apitalism, the platformization of society and the impact of disinformation on democracy, as well as its political uses. We also extensively discuss the multiple relationships between fake news, teaching and society. We analyzed the 14 collections approved in the National Textbook Program - PNLD - 2021, uantifying the definitions of fake news and the content in which the topic was addressed in these books. Based on the limits and possibilities present in hese collections, we propose a didactic material that can overcome the theoretical and methodological deficiencies of the books and guide teachers in the area of Applied Human and Social Sciences in High School. The didactic material is presented along three axes: a theoretical discussion on the definitions of fake news, the platformization of society and, finally, proposals for classroom activities. As a methodology, we used Simone Meucci's guidelines on how to analyze the textbook as a socio-cultural element present in a configurational logic of society, obeying editorial and economic imperatives